Peningkatan Kemampuan Matematika Anak Didik Pemasyarakatan dengan Program Holistik sebagai Upaya Peningkatan Kualitas Pendidikan - Rama Fatahillah Yulianto (Universitas Muhammadiyah Purwokerto, 2021)
Law Number 11 year 2012 concerning the Juvenile Criminal Justice System is a concrete manifestation of Restorative Justice, which regulates diversion, in which Law Enforcement Officials are obliged to seek diversion for children. So far, the education provided by the government for Children in Conflict with the Law is only limited to formal education and moral formation education, no less important than that mathematical ability should also be a concern for the government with a low level of mastery of mathematics in Indonesia. The learning model that emphasizes comfort and pleasure for children is considered to be very effective in teaching math skills to children at LPKA. This study aims to identify a learning model that is in accordance with the characteristics of education in LPKA. So that it is hoped that children after being free can integrate with the community and have the same abilities as children who are outside the institution, as well as improve the self-concept possessed by children. The benefits of this study can provide input in formulating policies regarding the education system in LPKA.Keywords: ABH, Diversion, Education